Impact of Community Radio on Agricultural Development in Southwest Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study investigates the impact of community radio on agricultural development in Southwest Nigeria. Using a survey design, data were collected from 100 respondents, comprising farmers actively engaged in agricultural activities. The findings reveal that community radio serves as a critical medium for disseminating agricultural knowledge, promoting the adoption of innovative practices, and improving farming productivity. A significant majority of respondents acknowledged that agricultural programs on community radio enhanced their knowledge of modern techniques, contributed to higher yields, and informed their decision-making. However, challenges such as poor signal quality, limited access to affordable radio devices, and inadequate agricultural content hinder the optimal utilization of community radio. The study adopts Development Communication Theory which was primarily propounded by Everett M. Rogers in 1962 and Diffusion of Innovations Theory, further expanded by Wilbur Schramm in 1964, emphasizing on the role of communication in promoting social change and development, particularly in rural settings. Recommendations include improvement of Signal Quality that the government and radio stations should invest in infrastructure to enhance signal strength and expand the reach of community radio to remote areas. This research underscores the transformative potential of community radio in addressing agricultural challenges and fostering rural development.